Perceptual Analysis of the Urban Green Infrastructure in Madrid Using NVIVO Software - Rocío Santo-Tomás Muro (2021)
The study of landscape in general, and green infrastructure in particular, is particularly complex, mainly to address the perceptual aspects required for any characterization. The use of a qualitative analysis for the study of perception in the case studies allows us to delve into the details and nuances that arise when analyzing what the literature has referred to as the "non-expert" view of the landscape Goals; Methods In order to analyse the perception of urban green infrastructure, we use a qualitative methodology, supported by NVIVO software. The software is used to code the responses of a series of semi-structured interviews conducted in the case studies; metropolitan parks in the outskirts of the city of Madrid, to study their perception. For coding, a "decantation" process is used: starting with an open coding, followed by an axial coding, and ending with a selective coding, thus creating a hierarchy among the main concepts (called "nodes") that emerge during the interviews. Results (The proposed methodological analysis aims to understand the perception of the elements that are part of the green infrastructure network around Madrid. The results obtained show that these interview techniques provide significant results with a relatively small sample of interviews. After the development of this research, we have opted for the use of this nomenclature: "technical" and "everyday" to refer to the views to the landscape. Thus, we delve into the sense of place, connectivity, multifunctionality and accessibility of urban green infrastructure or the image of the city.